A colorimetric, sensitive, rapid, and simple diagnostic kit for the HLB putative causal agent detection - Stolowicz, Fabiana; Larocca, Luciana; Werbajh, Santiago; Parma, Yanil; Carrillo, Carolina; Ogas, Lorena; Agostini, Juan Pedro; Redes, Jonathan; Welin, Bjorn; Castagnaro, Atilio; Vojnov, Adrian (Frontiers Media, 2025)
Huanglongbing (HLB) is one of the most devastating diseases in citrus worldwide. The Gram-negative bacterial plant pathogen “Candidatus Liberibacter spp.” is phloem-limited and vectored by citrus psyllids. The species “Candidatus Liberibacter asiaticus” (C.Las) has been detected in Argentina, and its vector has been found in at least nine provinces. Early detection of C.Las is critical for a successful management of HLB disease. Currently, HLB molecular diagnosis is carried out by PCR, nested PCR, real-time PCR, or another combination of these techniques, which require purification of genomic DNA, sophisticated equipment, and highly trained personnel. We have developed a prototype of a sensitive colorimetric kit to detect C.Las based on the specific DNA isothermal amplification of this microorganism. The reaction buffer contains hydroxynaphthol blue (HNB), an indicator dye that turns from violet to blue/light blue when the DNA amplification reaction is positive. Similar sensitivity to visualize a positive reaction was observed between HNB loop-mediated isothermal amplification and agarose gel electrophoresis analysis. The detection of C.Las-infected plants was up to 8 ng of total infected plant genomic DNA, similar to quantitative PCR. A blind validation test of the prototype kit was performed with purified DNA extracted from healthy or C.Las-infected midrib plants. Our kit showed 100% concordance with the results of a gold-standard quantitative PCR technique applied by the Laboratorio de Biología Molecular de EEA Montecarlo. The analysis of samples, without DNA purification to detect C.Las, showed a similar sensitivity to the analysis of the same samples in which C.Las DNA was previously purified.